Practice of Application in Cases of Terrorist Crimes, Problems of Law Enforcement (Global Journal of Human-Social Science, 2020)
This article provides an analysis of the rules on criminal responsibility for terrorism and hostage-taking and certain signs of corpus delicti The problem of qualification of terrorist crimes is relevant today One of the problems faced by the law enforcer who qualifies a terrorist act and hostagetaking is the correct determination of the signs of the composition of these related crimes In this article the authors analyze the norms of Art 205 of the Criminal Code and Art 206 of the Criminal Code the basic aspects of the differentiation of norms are disclosed the practice of law enforcement on the indicated compositions is studied
Keywords: terrorism; terrorist act; terrorist crimes; hostage taking; subject of crime; qualification problems; law enforcement practice